2011
DOI: 10.1002/ijc.26225
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing sunshine: A cross‐sectional survey of 500 Australian general practitioners' practices and attitudes about vitamin D

Abstract: This study aimed to assess the attitudes, practices and knowledge of general practitioners (GPs) with regards to vitamin D. A cross-sectional survey of a random sample of GPs stratified by location of practice (rural/remote or metropolitan) and employment status (full-time or part-time) in New South Wales (NSW), Australia was conducted. Of 500 respondents, 58.1% (95% CI 53.8-62.4) reported that up to 39% of their tested patients showed vitamin D deficiency or insufficiency and a further 37.7% (95% CI 33.5-41.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 25 publications
11
68
0
Order By: Relevance
“…Corresponding proportions in previous studies were 9% (Australia) and 6% (New Zealand). Surprisingly, while participants with darker skin are more at risk of insufficiency [1,38], they were the least concerned with their VitD status in our study, consistently with an Australian study on general practitioners [22] in which dark skin was not considered as a main risk factor for VitD insufficiency.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Corresponding proportions in previous studies were 9% (Australia) and 6% (New Zealand). Surprisingly, while participants with darker skin are more at risk of insufficiency [1,38], they were the least concerned with their VitD status in our study, consistently with an Australian study on general practitioners [22] in which dark skin was not considered as a main risk factor for VitD insufficiency.…”
Section: Discussionsupporting
confidence: 87%
“…Such information would be of interest for practitioners and public health institutions to improve the communication regarding VitD. Previous studies performed in several countries (mostly targeting specific groups) showed that VitD-related knowledge was limited [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. To our knowledge, no study was performed in a large European sample from the general population and few linked VitD-related knowledge to various individual characteristics (including measured VitD status).…”
Section: Introductionmentioning
confidence: 99%
“…Bonevski et al (2012) reported that some advice that general practitioners are providing may actually increase patients' risk for vitamin D insufficiency or skin cancer as a result of mixed attitudes and practices (Bonevski et al, 2012). Our findings somewhat alleviate this confusion, by showing that except for staying in the shade when spending a relatively short time outdoors, the use of sun protection methods on a regular basis is not associated with vitamin D levels of Australians in a sub-tropical community.…”
Section: Discussionsupporting
confidence: 41%
“…In this regard, despite sufficient evidence on the various determinants of vitamin D deficiency including lack of sun exposure and dietary intake, studies conducted on general practitioners, university and school students, general adult populations, and athletes mostly found participants to have inadequate knowledge regarding the role of sunlight in vitamin D production, the function and sources of vitamin D, and also negative attitudes and behaviors toward sunlight [11,12,13,14,15,16,17,18,19,20,21]. Hence, it seems understanding individuals’ knowledge, attitude and practice (KAP) regarding vitamin D is essential in developing related health promotion programs.…”
Section: Introductionmentioning
confidence: 99%